2020
DOI: 10.12688/wellcomeopenres.15837.2
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Co-existence of sarcoidosis and Takayasu arteritis

Abstract: Takayasu arteritis is a rare systemic large vessel vasculitis affecting the aorta and its branches. Sarcoidosis, too, is an inflammatory disease. Both entities are granulomatous conditions with a questionable association in their etiopathogenesis. Only a few cases of their coexistence have been reported in the literature. To our knowledge, no such cases have been reported from Nepal. We report a Nepalese woman who presented with non-productive cough, progressive shortness of breath and chest tightness of 3 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…This is supported by studies that showed that cardiomyocytes in CS patients upregulate the expression of tissue factor pathway inhibitor (TFPI) which is implicated in IL-1 signaling as well as angiogenesis (49). In addition, there have been several case reports describing CS patients who develop vasculitis towards the end-stage of their disease (50,51). This suggests that CS might be mediating this endothelial cell inflammation.…”
Section: Discussionmentioning
confidence: 93%
“…This is supported by studies that showed that cardiomyocytes in CS patients upregulate the expression of tissue factor pathway inhibitor (TFPI) which is implicated in IL-1 signaling as well as angiogenesis (49). In addition, there have been several case reports describing CS patients who develop vasculitis towards the end-stage of their disease (50,51). This suggests that CS might be mediating this endothelial cell inflammation.…”
Section: Discussionmentioning
confidence: 93%
“…Multiple case reports and small case series have documented that the inflammatory dysregulation in sarcoidosis can lead to vasculitis 3–15 . The most common vasculitic manifestation is cutaneous vasculitis, although published case reports indicate that any vessel size can be impacted 5,12,15 .…”
mentioning
confidence: 99%
“…2 Multiple case reports and small case series have documented that the inflammatory dysregulation in sarcoidosis can lead to vasculitis. [3][4][5][6][7][8][9][10][11][12][13][14][15] The most common vasculitic manifestation is cutaneous vasculitis, although published case reports indicate that any vessel size can be impacted. 5,12,15 Cutaneous manifestations of vasculitis in patients with sarcoidosis include palpable purpura, ulcerations, bullous formation, and the development of nodules.…”
mentioning
confidence: 99%